Psychoacoustic and Archeoacoustic nature of ancient Aztec skull whistles - Sascha Frühholz; Pablo Rodriguez; Mathilde Bonard; Florence Steiner; Marine Bobin (Communications Psychology)
Abstract Many ancient cultures used musical tools for social and ritual procedures, with the Aztec skull whistle being a unique exemplar from postclassic Mesoamerica. Skull whistles can produce softer hiss-like but also aversive and scream-like sounds that were potentially meaningful either for sacrificial practices, mythological symbolism, or intimidating warfare of the Aztecs. However, solid psychoacoustic evidence for any theory is missing, especially how human listeners cognitively and affectively respond to skull whistle sounds. Using psychoacoustic listening and classification experiments, we show that skull whistle sounds are predominantly perceived as aversive and scary and as having a hybrid natural-artificial origin. Skull whistle sounds attract mental attention by affectively mimicking other aversive and startling sounds produced by nature and technology. They were psychoacoustically classified as a hybrid mix of being voice- and scream-like but also originating from technical mechanisms. Using human neuroimaging, we furthermore found that skull whistle sounds received a specific decoding of the affective significance in the neural auditory system of human listeners, accompanied by higher-order auditory cognition and symbolic evaluations in fronto-insular-parietal brain systems. Skull whistles thus seem unique sound tools with specific psycho-affective effects on listeners, and Aztec communities might have capitalized on the scary and scream-like nature of skull whistles.